Effective medium approximation for conductivity of coated-inclusion composites with anisotropic coating - Viet, Tran Bao; Giang, Nguyen Thi Huong; Chinh, Pham Duc (Vietnam Journal of Mechanics, 2019)
Effective medium approximations are constructed in this paper to estimate the macroscopic conductivity of coated-inclusion composites with thin anisotropic coating. The two-phase coated-inclusion are substituted by equivalent one-phase inclusion, using the multi-coated spheres assemblage and the differential substitution approaches. Then, the usual effective medium approximation schemes are applied to the equivalent medium to estimate the conductivity of original three-phase composites. The results obtained were compared with the numerical simulation by finite element method in 2D show the effectiveness of the methods.